INCOME INEQUALITY – PERSPECTIVES FROM THE MAIN SCHOOLS OFECONOMIC THOUGHT - Bratoeva-Manoleva, Silviya (E-Journal VFU, 2025)
In recent decades, we have witnessed a growing income inequality, which hasbecome one of the most discussed topics, raising concern within society. Understanding themechanisms of income formation, distribution and redistribution has become exceptionallycrucial for this reason. The article aims to present the various perspectives of major economictheories on income inequality. The analysis reveals the complexity and multifaceted nature ofthe concept of income inequality, contributing to a more in-depth assessment of the forcescontributing to its formation.
Keywords: economic theory; income inequality; income distribution